Participatory Budgeting as if Emancipation Mattered - and Baiocchi, Gianpaolo; Ganuza, Ernesto (Politics & Society, 2014)
Participatory Budgeting has by now been widely discussed, often celebrated, and is now instituted in at least 1,500 cities worldwide. Some of its central features—its structure of open meetings, its yearly cycle, and its combination of deliberation and representation—are by now well known. In this article, however, we critically reflect on its global travel and argue for more careful consideration of some of its less well-known features, namely the coupling of the budgeting meetings with the exercise of power. We disaggregate PB into its communicative and empowerment dimensions and argue that its empowerment dimensions have usually not been part of its global expansion—and this is cause for concern from the point of view of emancipation. We thus discuss the specific institutional reforms associated with empowerment in the original version as well as its analytic dimensions. We also address some of the specific dangers of a communication-only version of PB as well as some suggestions for reintroducing empowerment.